Direct activation of zebrafish neurons by ultrasonic stimulation revealed by whole CNS calcium imaging. (13th October 2020) - Meneghetti, N; Dedola, F; Gavryusev, V; Sancataldo, G; Turrini, L; de Vito, G; Tiso, N; Vanzi, F; Carpaneto, J; Cutrone, A; Pavone, F Saverio; Micera, S; et al.
Abstract: Objective . Ultrasounds (US) use in neural engineering is so far mainly limited to ablation through high intensity focused ultrasound, but interesting preliminary results show that low intensity low frequency ultrasound could be used instead to modulate neural activity. However, the extent of this modulatory ability of US is still unclear, as in in vivo studies it is hard to disentangle the contribution to neural responses of direct activation of the neuron by US stimulation and indirect activation due either to sensory response to mechanical stimulation associated to US, or to propagation of activity from neighboring areas. Here, we aim to show how to separate the three effects and assess the presence of direct response to US stimulation in zebrafish. Approach . We observed in zebrafish larvae brain-wide US-induced activity patterns through calcium imaging microscopy. Sensory response to mechanical stimulation was assessed with a US shield. Activity propagation was assessed with inter-area latency evaluation. Main results . We prove that in selected brain regions the zebrafish's neural response is mainly due to direct activation, later spreading to the other regions. Shielding the neurons from direct US stimulation resulted in a significantly attenuated response, showing that sensory stimulation does not play a prominent role. Significance . US non-invasive neuromodulatory approach might lead to novel ways to test and control neural activity, and hence to novel neuromodulatory therapies. Future studies will focus on the biophysical structure of directly responsive neurons to capture the mechanisms of US induced activity.